THE ROLE OF PRESIDENT B.J. HABIBIE IN OVERCOMING ECONOMIC CRISIS IN INDONESIA IN THE 1998-1999 - Agung Mike Wijaya; Marjono Marjono; Sugiyanto Sugiyanto (History Education, University of Jember, 2020)
The prolonged economic crisis in Indonesia since the middle of 1997 began with the falling value of the Thai bath currency which influenced the social, economic and political life in Indonesia. The resignation of President Soeharto was replaced by B.J. Habibie as president with a policy direction that emphasizes the people's economic system. At the beginning of his reign, President B.J. Habibie was faced with problems such as the weaker banking system, the corporate world went bankrupt, and the high level of poverty. President B.J. Habibie's trade in overcoming the economic crisis embodied in the policy, among others, the restructuring of banks, the implementation of the social safety net (JPS) program, and the empowerment of the people's economy. Policies commited by President B.J. Habibie gained support from the Indonesian people, and gradually showed a positive picture of Indonesia towards recovery and improvement due to the economic crisis. The Indonesian economy is improving as indicated by the stability of national finance, the corporate world is increasing, and the poverty rate is declining. Keywords: B.J Habibie, Economic Crisis.